Macroporous photothermal bilayer evaporator for highly efficient and self-cleaning solar desalination. (November 2020) - Lee, Jaehyeon; Kim, Kiwoong; Park, Sung Ho; Yoon, Gun Young; Kim, Jeongju; Lee, Sang Joon
Abstract: Solar steam generation is a promising technology for harvesting solar energy to purify seawater and wastewater. State-of-the-art technologies have struggled to achieve sufficient solar evaporation rate and antifouling property simultaneously. In addition, the antifouling strategies based on flow dynamics need to be established to develop more efficient membrane designs. Here we propose a new superhydrophilic thermally-insulated macroporous membrane (STIMM) composed of carbonized sucrose and polydimethylsiloxane as an efficient solar evaporator. The converted solar energy is fully utilized for evaporation by the aid of the coupled effects of superhydrophilicity and heat localization. STIMM achieves a high evaporation rate of 2.045 kg/m 2 /h even at its macropore size under 1 sun irradiation, overcoming the previous trend limit. The macropores of STIMM enable self-cleaning with a 93.1% salt rejection rate. The high evaporation rate and geometrical traits of STIMM generate strong convective flows to dynamically reject salt. The solar desalination system based on STIMM stably produces a practically high amount of purified water with a production rate of 24.9–30.6 L/m 2 /day. Our proposed STIMM demonstrates a new paradigm for facile desalination systems that are low cost, energy efficient, and self-cleaning under natural environmental condition. Graphical abstract: Image 1 Highlights: 3D bilayer macroporous membrane is developed for efficient and sustainable solar steam generation. Superhydrophilicity of the membrane compensates for the evaporation limit at large pore sizes. Macropores of the membrane promote sedimentation of precipitated salt crystals for sustainable seawater desalination. High evaporation rate and geometrical traits of STIMM generate strong convective flows for dynamic salt rejection.